Heart involvement in cystic fibrosis: A specific cystic fibrosis-related myocardial changes?. (September 2016) - Labombarda, Fabien; Saloux, Eric; Brouard, Jacques; Bergot, Emmanuel; Milliez, Paul
Abstract: Cystic fibrosis is a complex multi-systemic chronic disease characterized by progressive organ dysfunction with development of fibrosis, possibly affecting the heart. Over the last four decades pathological, experimental, and clinical evidence points towards the existence of a specific myocardial involvement in cystic fibrosis. Multi-modality cardiac imaging, especially recent echocardiographic techniques, evidenced diastolic and/or systolic ventricular dysfunction in cystic fibrosis leading to the concept of a cystic fibrosis-related cardiomyopathy. Hypoxemia and inflammation are among the most important factors for heart involvement in cystic fibrosis. Cystic Fibrosis Transmembrane Regulator was found to be involved in the regulation of cardiomyocyte contraction and may also account for cystic fibrosis-related myocardial dysfunction. This review, mainly focused on echocardiographic studies, seeks to synthesize the existing literature for and against the existence of heart involvement in cystic fibrosis, its mechanisms and prognostic implications. Careful investigation of the heart function may be helpful for risk stratification and therapeutic decisions in patients with cystic fibrosis. Highlights: Pathological, experimental, and clinical evidence suggest the existence of specific myocardial involvement in cystic fibrosis. Clinical relevancy of the cardiac abnormalities in cystic fibrosis remains to be precised. Hypoxemia and inflammation are important contributors for heart involvement in cystic fibrosis. Careful modality of the heart function may help for risk stratification and therapeutic decisions in patients with cystic fibrosis.